GATHERING COORDINATES OF THE GEOLOGICAL AND GEOTECHNICAL LOCATION OF THE MINE (British Journal of Global Ecology and Sustainable Development, 2023)
The identification and mitigation of adverse geologic conditions are critical to the safety and productivity of underground coal mining operations. To anticipate and mitigate adverse geologic conditions, a formal method to evaluate geotechnical factors must be established. Each mine is unique and has its own separate approach for defining what an adverse geological condition consists of. The collection of geologic data is a first critical step to creating a geological database to map these hazards efficiently and effectively. Many considerations must be taken into account, such as lithology of immediate roof and floor strata, seam height, gas and oil wells, faults, depressions in the mine floor (water) and increases in floor elevation (gas), overburden, streams and horizontal stress directions, amongst many other factors. Once geologic data is collected, it can be refined and integrated into a database that can be used to develop maps showing the trend, orientation, and extent of the adverse geological conditions. This information, delivered in a timely manner, allows mining personnel to be proactive in mine planning and support implementations, ultimately reducing the impacts of these features. This paper covers geologic exploratory methods, data organization, and the value of collecting and interpreting geologic information in coal mines to enhance safety and production. The implementation of the methods described above has been proven effective in predicting and mitigating adverse geologic conditions in underground coal mining. Consistent re-evaluation of data collection methods, geologic interpretations, mapping procedures, and communication techniques ensures continuous improvement in the accuracy of predictions and mitigation of adverse geologic conditions. Providing a concise record of the work previously done to track geologic conditions at a mine will allow for the smoothest transition during employee turnover and transitions. With refinements and standardization of data collection methods, such as those described in this paper, along with improvement in technology, the evaluation of adverse geologic conditions will evolve and continue to improve the safety and productivity of underground coal mining.